2010
DOI: 10.1111/j.1750-3841.2010.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural Antimicrobial Substances in Red Muscadine Juice against Cronobacter sakazakii

Abstract: Red muscadine (Vitis rotundifolia Michx.) juices with natural organic, phenolic acids and polyphenol compounds were tested against Cronobacter sakazakii. The concentration of total phenolic compounds of commercial baby juices ranged from 176.7 to 347.7 mg/mL. Commercial baby juices showed poor antimicrobial activity, reducing less than 1-log of C. sakazakii in juice samples for 2 h at 37 degrees C. Red muscadine juices, regardless of processing methods (filtration, pasteurization, and sterilization), achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Several reports have described the effect of natural antibacterial substances, including blueberry proanthocyanidins and commercial blueberry juice (Joshi et al, 2014), carvacrol and thymol (Lee & Jin, 2008), caprylic acid, citric acid, and vanillin (Choi, Kim, Lee, & Rhee, 2013), trans-cinnamaldehyde (Amalaradjou, Hoagland, & Venkitanarayanan, 2009), water-soluble muscadine seed extracts (Kim, Kim, & Jung, 2008) and red muscadine juice (Kim, Weng, Silva, Jung, & Marshall, 2010). However, in many cases, the antimicrobial effects of these plants substances were measured with a rehydrated infant milk formula (RIMF) model.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have described the effect of natural antibacterial substances, including blueberry proanthocyanidins and commercial blueberry juice (Joshi et al, 2014), carvacrol and thymol (Lee & Jin, 2008), caprylic acid, citric acid, and vanillin (Choi, Kim, Lee, & Rhee, 2013), trans-cinnamaldehyde (Amalaradjou, Hoagland, & Venkitanarayanan, 2009), water-soluble muscadine seed extracts (Kim, Kim, & Jung, 2008) and red muscadine juice (Kim, Weng, Silva, Jung, & Marshall, 2010). However, in many cases, the antimicrobial effects of these plants substances were measured with a rehydrated infant milk formula (RIMF) model.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, researchers have found that organic acids can inhibit the growth of some bacteria and fungi. Kim et al (2010) reported that red muscadine juice, which is rich in organic acids, showed strong antimicrobial action against Cronobacter sakazakii, and the main organic acids present were malic and tartaric acids. Raybaudi-Massilia et al (2009) discovered that malic acid could inhibit the growth of Listeria monocytogenes, Salmonella gaminara, and Escherichia coli O157: H. Eswaranandam et al (2004) also found that organic acids such as malic, citric, lactic, and tartaric acid had antibacterial activity with specific pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been proposed to control the risk associated with Cronobacter contamination, including the use of antimicrobial compounds that can reduce thermal tolerance during rehydration in hot water and/or inhibit growth in reconstituted dried foods (1,3,20,25,26,28,36,43). Vanilla extracted from the bean or pod of the vanilla orchid (Vanilla planifolia Andrews, syn.…”
mentioning
confidence: 99%